Surgical and prosthetic management of difficult cases of edentia – case report - Wiśniewska, Grażyna; Orczykowska, Magdalena; Pihut, Małgorzata (Journal of Stomatology, 2017)
Introduction: The most important factors influencing the course and outcome of toothless issues related to anatomical and physiological conditions of the prosthetic base. Atrophied substrate prosthetic and incorrect centric relation , creating from the point of view of biomechanics, poor fixation and stabilization of prostheses. In such cases it is necessary to appropriate treatment as clinical and laboratory, to achieve a satisfactory result of treatments. Objective: Presentation of procedures surgical and prosthetic that can be used in difficult cases toothless, for example the description of a clinical case of the patient being treated. Material and Methods: The patient in the first stage was carried out surgical correction of prosthetic base, and at the time of wound healing was used appropriately underlain been utilized prosthesis. After healing wounds, used dentures made by the biofunctional system. Efficacy was evaluated on the basis of clinical criteria, subjective assessment of the functioning of dentures, including the results of research involving instrumental analysis of the occlusion using the camera T-Scan, electromyographic measurement of muscle tension and mechanical measurement of the forces of chewing. Research instrumental performed on previously utilized prostheses and one month after the application of new dentures. Results: For all evaluated criteria, better results were obtained after the surgical preparation of the substrate and the use of prostheses made according biofunctional system. It can be concluded that the rehabilitation prosthetic conducted by the described procedure can be recommended for use in difficult cases toothless prosthetic base. Conclusion: Prosthetic rehabilitation carried out by the described procedure can be recommended for use in difficult cases toothless prosthetic base.